2018
DOI: 10.3233/jad-180069
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Local Potential Participant Registry to Improve Alzheimer’s Disease Clinical Research Recruitment

Abstract: Potential participant registries are tools to address the challenge of slow recruitment to clinical research. In particular, registries may aid recruitment to secondary prevention clinical trials for Alzheimer's disease (AD), which enroll cognitively normal older individuals meeting specific genetic or biomarker criteria. Evidence of registry effectiveness is sparse, as is guidance on optimal designs or methods of conduct. We report our experiences of developing a novel local potential participant registry tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…Improvements in equipment and technique have reduced risk of pain and post-dural puncture headaches, yet lingering negative attitudes toward the procedure continue to impede CSF research. For example, while 4 in every 5 enrollees of our C2C Registry express willingness to be contacted for studies involving positron emission tomography imaging (and 9 in every 10 for magnetic resonance imaging), less than half agree to be contacted for studies involving LP (14). In this study, we found that 43% of these registry enrollees who completed an educational intervention changed their response to be willing to consider research involving LP.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Improvements in equipment and technique have reduced risk of pain and post-dural puncture headaches, yet lingering negative attitudes toward the procedure continue to impede CSF research. For example, while 4 in every 5 enrollees of our C2C Registry express willingness to be contacted for studies involving positron emission tomography imaging (and 9 in every 10 for magnetic resonance imaging), less than half agree to be contacted for studies involving LP (14). In this study, we found that 43% of these registry enrollees who completed an educational intervention changed their response to be willing to consider research involving LP.…”
Section: Discussionmentioning
confidence: 72%
“…Participants were recruited from the University of California at Irvine Consent-to-Contact (C2C) Registry, a local, online research recruitment registry (14). Adults age 18 years and older who had enrolled in the C2C Registry and had indicated that they were not willing to be contacted about studies requiring LP were eligible to participate.…”
Section: Participantsmentioning
confidence: 99%
“…Because AD trial participation is necessarily the work of a dyad, if an otherwise eligible individual cannot identify a study partner, he or she cannot enroll. For example, more than a quarter of registrants (333 out of 1202) in the UC Irvine Consent-to-Contact (C2C) Registry answered “no” when asked “Is there an individual who could join you at research visits, such as a spouse, family member, or friend?” [ 18 ]. At present, it is unknown how often individuals screen-fail for clinical trial participation because they cannot or will not identify a study partner.…”
Section: Introductionmentioning
confidence: 99%
“…Research registries represent an emergent methodology for enhancing recruitment and retention efforts [21]. Registries consist of a longitudinal database containing basic demographic characteristics and health information regarding potential research participants.…”
Section: Introductionmentioning
confidence: 99%